2022
DOI: 10.3390/f13111810
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Forest Management Research in the Context of Carbon Neutrality: A Bibliometric Analysis

Abstract: Climate change has become a threat to humanity, and achieving carbon neutrality is a worldwide objective. Forests are significant natural carbon sinks; forest ecosystems are one of the effective ways to mitigate climate change, and professional management may effectively contribute to achieving carbon neutrality goals. Using the bibliometrix R-package in R and CiteSpace for bibliometric analysis of research areas from general statistics and knowledge base perspectives, this study systematically reviewed the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…The search results showed that the number of bibliometric studies in envi-ronmental science increased from 7 in 2005 to 1027 in 2022. Among all these bibliometric studies in environmental science, nine of them focused on carbon neutrality in the building sector [31], in the construction industry [32], from the global health perspective [33], from the forest management perspective [34], research changes due to the COVID-19 [35], and in a general sense [36][37][38][39]. Additionally, there was another bibliometric study on climate change that has implications on carbon neutrality [40].…”
Section: Methodsmentioning
confidence: 99%
“…The search results showed that the number of bibliometric studies in envi-ronmental science increased from 7 in 2005 to 1027 in 2022. Among all these bibliometric studies in environmental science, nine of them focused on carbon neutrality in the building sector [31], in the construction industry [32], from the global health perspective [33], from the forest management perspective [34], research changes due to the COVID-19 [35], and in a general sense [36][37][38][39]. Additionally, there was another bibliometric study on climate change that has implications on carbon neutrality [40].…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometric analysis is a method that quantifies development of research in different fields and identify relevant trends; it studies the development process of academic research areas, recognize current pertinent themes, and predict future research directions (Aria & Cuccurullo, 2017). Along with visual mapping generated by bibliometric software, bibliometric analysis provides a systematic and detailed description of the knowledge context of the research area (Martínez et al, 2015;Zhang et al, 2022). The research reported in this article could help researchers interested in working within the NbS research area to identify relevant topics, information needs or themes with most advances in the NbS area related to climate change, water, and biodiversity crisis at different scales and government levels.…”
Section: Introductionmentioning
confidence: 99%